Reconciling the conservation of endangered species with economically important anthropogenic activities: interactions between cork exploitation and the cinereous vulture in Spain - Margalida, A; Moreno-Opo, R; Arroyo, B E; Arredondo, A (Animal Conservation, 2011)
Limitation of disturbing activities around the breeding areas of protected species is not always possible, if these activities are economically important and have, in addition, positive effects on protecting the habitats of those protected species. Searching for optimal solutions making commercial exploitation of natural resources compatible with biodiversity conservation is thus of concern to managers and policy makers. This is the case of the cinereous vulture Aegypius monachus, breeding primarily in cork-oak woodland, and cork exploitation, a traditional socio-economic activity carried out in several Mediterranean countries, and critical for the maintenance of this important habitat. We studied the effects of this anthropogenic activity on the behaviour and breeding success of breeding cinereous vultures in Spain. For the adults, the probability of nest abandonment was dependent on the distance of workers from the nest and the level of noise; activities within 500 m from the nest were likely to cause abandonment of the nest by adults, if the level of noise was intermediate or loud. Neither the size of the working group nor the use of machines per se, had any effect on the probability of nest abandonment. Pairs in an area of the colony exposed to intrusive anthropogenic activity had 20% lower breeding success than those in the same colony that were not exposed to these disturbances. If the application of buffer zones of 500 m is not possible (as is likely given the economic losses involved), several alternatives are recommended based on our results to minimize the impact of these activities, in particular to diminish the noise level of cork extraction activities. Observational studies like this help understanding the magnitude of the problem and finding alternative solutions for harmonizing conservation and economic development.
Keywords: buffer zone; cork harvesting; economic anthropogenic activity; Human disturbance; vulture conservation